2009
DOI: 10.1140/epja/i2009-10817-3
|View full text |Cite
|
Sign up to set email alerts
|

Charge radii and magnetic moments of odd- A 183-189Pb isotopes

Abstract: Isotope shifts and hyperfine splitting parameters have been measured for the neutron-deficient odd-mass lead isotopes [183][184][185][186][187][188][189] Pb. The measurement was performed at the ISOLDE (CERN) online mass separator using the in-source resonance ionization spectroscopy technique. The nuclear root mean square charge radii r 2 and the electromagnetic moments μ and QS have been deduced. They follow the smooth trend of the heavier isotopes and indicate the absence of deformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…No γ-ray has been seen coincident with the 5727 and 5764 keV α particles. These two γ-rays were also observed in our 185 Tl The hyperfine spectra corresponding to the 13/2 and 3/2 states of the neutron-deficient Pb nuclei are very different and well identified [12,39]. The intensity variations of the α lines with the laser beam frequency have provided the hyperfine spectra shown in fig.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…No γ-ray has been seen coincident with the 5727 and 5764 keV α particles. These two γ-rays were also observed in our 185 Tl The hyperfine spectra corresponding to the 13/2 and 3/2 states of the neutron-deficient Pb nuclei are very different and well identified [12,39]. The intensity variations of the α lines with the laser beam frequency have provided the hyperfine spectra shown in fig.…”
Section: Resultssupporting
confidence: 68%
“…In recent years, the deformation evolution of the neutron-deficient 182−190 Pb nuclei was investigated by in-source laser spectroscopy. The changes in nuclear charge radius and the nuclear-moment values have already been published [11,12]. These results have shown that the Pb nuclei in their isomeric and ground states keep a quasi-spherical shape even far from the valley of stability.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Following the series of experiments on the study of nuclear spins and electromagnetic moments of Cu isotopes [56,[78][79][80] the in-source RIS collaboration has performed extensive laser and nuclear-spectroscopic studies of isotopes in the lead region, namely the Tl [81], Pb [70,[82][83][84], Hg [45], Bi [85], Po [43,77,86,87], At and Au chains [22,88]. Our recent activity in this field has revisited the neutron-deficient Au and Hg isotopes, which were first studied at ISOLDE approximately four decades ago: the very first optical spectroscopy experiments performed at an ISOL facility [89][90][91][92].…”
Section: In-source Rismentioning
confidence: 99%
“…These phenomena are manifested, among other observables, by the large odd-even staggering in the charge radii [6]. More recently, the studies in the long chain of the lead (Z = 82) isotopes revealed that these nuclei remain essentially spherical in their ground states down to N = 102 [7,8] despite the presence of low-lying states with different shapes [3].…”
Section: Introductionmentioning
confidence: 99%